Rural development policies and sub-national governance: The case of the leader axis in Peloponnesus Greece - Helen Caraveli; Anastassios Chardas (European Regional Science Association (ERSA), 2013)
The new model of agricultural policy in Europe, applied through the rural development programs (RDPs), has been considered most appropriate for the case of Greece, given the structural problems of this country?s farm sector (including the high proportion of mountainous, less favoured areas in the country?s territory) and the new wave of return migration to rural areas ? as a result of the uneven regional impact that the current crisis and the austerity measures it led to have had for regions exposed to the global vicissitudes (i.e. urban areas and former industrialized regions). An integral part of the rural development policy of the CAP is a decentralized type of governance, based on a ?bottom-up? approach and implemented through the Leader programs. Within this context, regional and local actors, state or private, are assigned a substantial role in designing and implementing RDPs in their localities through the creation of horizontal or vertical synergies. Though the Leader philosophy can be instrumental in the successful application of RDPs in Greek rural regions (possibly aided by the new administrative division ? the Kallicrates), it has been rather little researched and investigated. This paper aims at ?filling this gap? in the literature by examining the possibilities of introducing the bottom up approach in the governance of rural regions in Greece, where the old-type ?sectoral? (vs. the holitistic development) approach continues to dominate agricultural policy and where local decisions have traditionally (and certainly in the last 30 years or so) been controlled and directed by the central state. A crucial question is can the leader-based type of governance help in the regeneration of the country-side and the promotion of internal cohesion in Greece? The methodology basically includes a comparison between leader programs of various periods as well as between the bottom-up approach and the one prevailing before the adoption of the Community Support Frameworks (CSFs).
Keywords: 330; Rural Development Programs; Greek Leader; bottom-up approach; Community Support Frameworks in Greece; Cohesion Policy